The short second life of Bree Tanner : an Eclipse novella - Meyer, Stephenie, 1973- (Little, Brown and Company, 2010)
Bree and Diego are newborn vampires created by a mysterious creature to be pawns in a game. They realize they must choose a side, but they don't know whom to trust.